Represi Terhadap Incest (Kajian Mengenai Kasus Incest di Kabupaten Aran Pandang) - Andi Tyas Surya Nugraha (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
The issue of sexuality is always interesting to be discussed,which is very much the language contained in the discourse.Included is incest, which in Indonesian society are consideredand reworded as illness, irregularities, and enter the realm ofcrime. Settlement of the issue of incest in Indonesia curative.The new issue decided upon its completion after it happened inthe middle of them. One is through the imprisonment ofperpetrators of incest, in this case the father intercourse with hisbiological child. In this incest problem is not only to show thatthere is repression against the perpetrators of the body only,but there are mechanisms of repression through languageinherent in the subject (people). This has encouraged the subjectto blame or stigma given to life, as perverts, sinners, and so on.Besides language stating that the discussion of incest inparticular or in general sex is taboo, making this issue difficultto unfold and always hidden. Because such talk is forbidden tothe public, because it was considered unethical. So while thereis repression either through natural language in the subjectunconscious or physically massive and evolving, but theincidence of incest continues to exist.Keywords: Language, Repression, Incest, Subject, Promiscuity,Structure